Pain and removal force associated with bracket debonding: a clinical study (Journal of Applied Oral Science, 2021)
Objective: Pain is a problem during bracket removal, and more comfortable treatment is needed. This study examined the association of pain with the removal force required for ceramic brackets, compared with metal and plastic brackets, to determine which removal method resulted in less pain and discomfort. Methodology: 81 subjects (mean age, 25.1 years; 25 males and 56 females) were enrolled, from whom 1,235 brackets (407 ceramic, 432 plastic, and 396 metal) were removed. Measured teeth were distinguished at six segments. Pain was measured with a visual analogue scale (VAS) during the removal of each bracket. An additional grip was placed on the grips of debonding pliers with right-angled beaks; a mini loading cell sensor pinched by the grips was used to measure removal force during debonding. VAS and force values were statistically analyzed. The Kruskal–Wallis test followed by the Mann–Whitney U test with Bonferroni correction were performed for multiple comparisons; multiple regression analysis was also performed. Results: Forces in the upper and lower anterior segments were significantly smaller (p<0.05) than those in the other segments. Pain tended to be greater in the upper and lower anterior segments than in the posterior segments. In all segments, the removal force was greater for metal brackets than for plastic or ceramic brackets. Ceramic brackets caused significantly greater pain than plastic brackets for the upper and lower anterior segments. Debonding force was involved in the brackets, following adjustments for pain, upper left segment, age, and sex. Conclusions: Pain and discomfort are likely to occur during bracket debonding.